The phase of love in the lyrics of the song “di timur” by Sal Priadi (Semiotic analysis) - Choirunnisa', Amellia; Alfian Setya Nugraha (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The purpose of this research is to examine and interpret the lyrics of a song entitled "Di Timur" on one of Sal's albums entitled "Be careful". The researchers focused on the meaning and signs contained in the lyrics of the song "Di Timur". The method used by researchers is a qualitative research method with hermeneutic analysis techniques, which in this hermeneutic technique has a relationship with examining and interpreting in depth the object being studied. The researcher uses Semiotics theory to dissect and clarify song lyrics as the object of research. In Charles Sanders Pierce's semiotics there is a focus on Signs, Objects, and Interpretants which are commonly known as the triangle of meaning. The researcher conducted an analysis in studying the lyrics of the song "Di Timur" by Sal Priadi using Charles Sanders Pierce's Semiotics theory, so a data was found in the form of the phenomenon of the love phase which could be studied again in depth to get the meaning and signs implied in the lyrics of the song "Di Timur" " the. examines the lyrics of the song "Di Timur" by classifying objects into signs, objects, and interpretants. The phenomenon of the love phase implied in the lyrics of the song "Di Timur" includes the infatuation phase, the calm phase, the stormy phase, the stable phase, and the unconditional love phase.Some of these things can be seen through the data found in the study.